PERAN BAWASLU DALAM MENCEGAH MONEY POLITICS DALAM PEMLIHAN GUBERNUR PROVINSI LAMPUNG TAHUN 2018 - Metria Shela; Sutiyo Sutiyo (P3M STISIPOL Dharma Wacana Metro, 2018)
Democracy and election implementation are like two sides of a coin that cannot be separated. The implementation of elections is one indicator of democracy in democratic countries. As a democratic country Indonesia conducts regional head elections at the level of the governor every five years. In Lampung Province a gubernatorial election was held in 2018. However, the implementation of the election was marked by money politics or the existence of money politics. Money politics is one of the violations in carrying out general elections. This paper aims to see the effectiveness of the role of the bawaslu in preventing money politics in the elections in Lampung Province in 2018. This study uses descriptive qualitative research, and uses secondary data types obtained from informants and uses data analysis techniques suggested by Miles and Hubberman (2002 ) which consists of data reduction, data display and conclusion drawing. This research concludes that the Bawaslu of Terbanggi Besar sub-district has carried out the task well but remains not optimal due to limited authority